LEGALITY OF CONSTRUCTION WORKING CONTRACTS AS AN FORMIL AGREEMENT - Diana Rahmawati; Zakiyah; Muhammad Arsyad (Lambung Mangkurat Law Journal, 2021)
The purpose of this study is to determine the form of construction work contracts and the legal consequences of construction work contracts that are not in accordance with the provisions of statutory regulations in the field of construction services. The legal research method used is normative legal research, which is a study of the prevailing laws and regulations which are particularly related to construction service contracts. This type of research is legal obscurity. A construction work contract is a type of formal agreement in which Law Number 2 of 2017 concerning Construction Services and its implementing regulations determines the procedures and conditions before the contract is made, including the form and content of the construction work contract, by determining the standard at a minimum, the contents of a construction service work contract that must be included in the construction work agreement by the parties. Since the construction work contract is a contract with mandatory conditions, the construction work contract is a formal agreement. This is if the construction work contract is made without paying attention to the provisions of laws and regulations in the field of construction services, both regarding the qualification requirements of a construction service provider, the procedure for selecting a service provider and the form and content of the construction service contract that has been determined by the law. As a juridical consequence, if the formal conditions are not fulfilled in a contract concerned, it is not legally enforceable or in other words it is a null and void contract (nietig, null and void).